Creating a mindful organisation by redefining PMS in police organisations: a balance scorecard approach. (2nd September 2020) - Kapuria, Monica; Balani, Sunita; Kaur, Prabjot
In order to orient police towards their respective key result areas, it is essential to implicate an innovative approach in facilitating the performance dynamics of policing so that a mindful organisation can be created. Therefore, this paper aims to propose an innovation in the working style of the policing by exploring the scope of strategic performance management system through the BSC intervention. The study is conducted to propose the strategic changes in the system by identifying the grey areas in the prevailing process with a recommendation to explore the scope of adoption of BSC in policing. Descriptive cross sectional research design is used for the study. Self developed questionnaire was administered to collect the primary data from 300 respondents including gazetted and non-gazetted police personnel. Stratified and quota sampling techniques were used. Two hundred twenty-nine questionnaires were found complete in all respect (with a response rate of 76.3%) and were thus made part of the study. Data was analysed using non-parametric techniques. It was found that, there is a discrepancy among the satisfaction level, expectations and perception of police personnel with respect to performance management system revealing the need for strategically aligned PMS for the department.